1997
DOI: 10.1001/archpsyc.1997.01830160040006
|View full text |Cite
|
Sign up to set email alerts
|

Adult Major Affective Disorder After Prenatal Exposure to an Influenza Epidemic

Abstract: These data are consistent with the hypothesis concerning the possible neurodevelopmental contribution to the origins of some forms of major affective disorder, especially unipolar depressive disorder. These encouraging findings, if replicated, may suggest that some mental disorders may stem, in part, from a disturbance in the development of the fetal brain during the second trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(120 citation statements)
references
References 32 publications
2
113
2
1
Order By: Relevance
“…Importantly, prenatal infections, as with other prenatal exposures known to influence the neurodevelopment of schizophrenia, may actually exhibit limited diagnostic specificity and thus also predict non-psychotic psychiatric disorders (Verdoux, 2004). Shortly after the relationship between prenatal influenza and offspring schizophrenia surfaced in ecological studies of influenza epidemics (Mednick et al, 1988), the hypothesized link was extended to include affective disorders, but the resulting literature failed to provide consistent evidence for this link (Brown et al, 1995;Machon et al, 1997;Morgan et al, 1997). More recently, Selton and Morgan reviewed the evidence across these ecological studies and concluded the affective disorders hypothesis could not be supported (Selten and Morgan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, prenatal infections, as with other prenatal exposures known to influence the neurodevelopment of schizophrenia, may actually exhibit limited diagnostic specificity and thus also predict non-psychotic psychiatric disorders (Verdoux, 2004). Shortly after the relationship between prenatal influenza and offspring schizophrenia surfaced in ecological studies of influenza epidemics (Mednick et al, 1988), the hypothesized link was extended to include affective disorders, but the resulting literature failed to provide consistent evidence for this link (Brown et al, 1995;Machon et al, 1997;Morgan et al, 1997). More recently, Selton and Morgan reviewed the evidence across these ecological studies and concluded the affective disorders hypothesis could not be supported (Selten and Morgan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported an association between bipolar disorder and stressful early life events such as gestational hunger (Brown et al, 2000), gestational influenza (Machon et al, 1997;Parboosing et al, 2013), childhood abuse (Daglas et al, 2014;Etain et al, 2008;Gilman et al, 2014) and early parental loss (Morotensen et al, 2003). Early life events that may induce circadian dysfunction are of particular interest since bipolar disorder involves the disruption of many biological rhythms affecting the 24 hour sleepwake cycle, energy and alertness (Giglio et al, 2009;McClung, 2013;Murray and Harvey, 2010;Wirz-Justice, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies conducted on women pregnant during the 1957 influenza epidemic provided some evidence of an association between influenza infection and development of bipolar disorders in offspring (18,80). These studies had several limitations, including diagnosis based on case notes, no differentiation of the manic-depressive from the depressive disorder, small sample sizes, and …”
Section: Infections and Psychiatric Disordersmentioning
confidence: 99%